The promise of a normal life : a novel - Gibson, Rebecca Kaiser (Arcade Publishing, 2023)
"The unnamed narrator is a fiercely observant, introverted Jewish-American girl who seems to exist in a private and separate realm. She's the child of a first-generation doctor and lawyer--whose own stories have the loud grandeur of family legend--in an America where Jews are excluded from the country club across the street. Her expectations for adulthood are often contradictory. In the changing landscape of the 1960s, she attempts to find her way through the rituals of life, her geography expanding across the country, across the ocean, and into multiple nations."--